Mental health in higher education students and non-students: evidence from a nationally representative panel study - Tabor, Evangeline (Soc Psychiatry Psychiatr Epidemiol, 2021)
Despite increasing policy focus on mental health provision for higher education students, it is unclear whether they have worse mental health outcomes than their non-student peers. In a nationally-representative UK study spanning 2010–2019 (N = 11,519), 17–24 year olds who attended higher education had lower average psychological distress (GHQ score difference =  − 0.37, 95% CI − 0.60, − 0.08) and lower odds of case-level distress than those who did not (OR = 0.91, 95% CI 0.81, 1.02). Increases in distress between 2010 and 2019 were similar in both groups. Accessible mental health support outside higher education settings is necessary to prevent further widening of socioeconomic inequalities in mental health. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s00127-021-02032-w.